K.H. Ahmad Dahlan dan Dinamika Pembaruan Islam: Telaah Historis atas Kepribadian, Gagasan, dan Kelahiran Muhammadiyah - Apris; Desi Asmaret; Julhadi; Syaifullah SA (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
This study aims to examine the life and personality of Kiai Haji Ahmad Dahlan from a historical and analytical perspective, focusing on his pioneering role in Islamic reform in Indonesia and the dynamics surrounding the birth and early development of the Muhammadiyah organization. The research employs a descriptive qualitative approach through library research, concentrating on the analysis of historical documents, scholarly works, as well as primary and secondary sources related to the figure and the Muhammadiyah movement. Data were collected using documentation techniques and analyzed descriptively and analytically through an inductive approach to formulate findings in a systematic and objective manner. The findings indicate that K.H. Ahmad Dahlan was a visionary Islamic reformer with a balanced character of scholarly depth, spiritual piety, and social concern. He not only promoted theological renewal grounded in the Qur’an and Sunnah but also manifested it through social movements via Muhammadiyah. This organization served as a medium for transformation through modern education, healthcare services, women’s empowerment, and various charitable initiatives. With its rational and structured approach, Muhammadiyah emerged as a representation of progressive Islam that is responsive to contemporary needs. These findings affirm that Ahmad Dahlan and Muhammadiyah are not merely part of Indonesia’s Islamic history but stand as a living model of Islam as a liberating and constructive force for a civilized and progressive society.